High-toughness temperature-resistant foaming material for FDM printing

By using PBAT resin and a non-crystalline resin with good compatibility in FDM printing materials, combined with appropriate foaming agents, the shortcomings of existing materials in impact and temperature resistance are solved, and a foaming material with high toughness and high temperature resistance are achieved, and the quality and use range of wires are improved.

CN119661993APending Publication Date: 2025-03-21SUZHOU MULTIFILAMENT LUOKE NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411703917.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing foaming materials used for FDM printing have shortcomings in impact and temperature resistance, and the foaming agent is prone to foaming in advance at high temperatures, affecting the quality of the wire.

Method used

A high-toughness and high-temperature foaming material using PBAT resin as the base material is added to add amorphous resin compatible with PBAT (such as PETG, PCTG, PC), microsphere foaming agent or carbonate foaming agent, and control the foaming temperature during the processing to make it lower than the processing temperature to avoid foaming of the foaming agent in advance.

Benefits of technology

The high toughness and high temperature resistance of the material are achieved, and the quality and use range of wires are improved by controlling the foaming ratio and density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661993A_ABST
    Figure CN119661993A_ABST
Patent Text Reader

Abstract

The invention discloses a high-toughness temperature-resistant foaming material for FDM (fused deposition modeling) printing, which is prepared from the following components in percentage by mass: 5 to 35 percent of first-class resin, 3 to 10 percent of second-class resin, 0.5 to 2 percent of a foaming agent and the balance of a lubricating agent. The first-class resin is PBAT (poly (butylene adipate-co-terephthalate)) resin, and the second-class resin is amorphous resin compatible with the PBAT resin. Through the mode, the requirements on processing characteristics can be met, the material is kept stable and cannot be excited in the processing process, the foaming ratio of the material can be automatically adjusted according to needs, the material can be converted between a soft foaming material and a hard foaming material by adjusting a formula, and the PLA-based material can be replaced in part of fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of 3D printing materials, and in particular to a high-toughness, temperature-resistant foaming material for FDM printing. Background Art

[0002] FDM (fused deposition modeling) technology is the most widely used 3D printing technology. Materials are one of the main technical bottlenecks for the further development of FDM technology. At present, the foaming consumables suitable for FDM technology are mainly PLA resin substrates. This type of material is mainly used in the fields of aircraft models, ship models, cosplay props, etc. Although it has achieved good responses, there are still some problems in practical applications. It is mainly manifested in its lack of impact resistance. Some bumps during use will cause the product to crack. At the same time, the temperature resistance of this type of material is usually only about 50°C, and it is easy to deform when exposed to sunlight when used outdoors. In order to solve the above problems, we began to use PBAT resin instead of PLA as the resin substrate. However, although PBAT resin has high heat resistance and high toughness, it has low hardness. After foaming, its hardness will be further reduced, which limits its scope of use. Therefore, it needs to be modified. In the prior art, it is usually melt-blended by adding polyester resins with good compatibility with it, but this type of resin usually has a high viscosity and needs to increase the processing temperature after blending. Adding a foaming agent in this process is likely to cause the foaming agent to foam prematurely due to high temperature, affecting the production quality of the final wire. Summary of the invention

[0003] The main technical problem solved by the present invention is to provide a high-toughness temperature-resistant foaming material for FDM printing, which can control the foaming temperature so that the foaming temperature is below the processing temperature, thereby improving the quality of the wire.

[0004] In order to solve the above technical problems, a technical solution adopted by the present invention is: to provide a high-toughness and heat-resistant foaming material for FDM printing, wherein the components of the high-toughness and heat-resistant foaming material include: a type-one resin, a type-two resin, a foaming agent and a lubricant, wherein the mass fraction of the type-two resin is 5-35%, the mass fraction of the foaming agent is 3-10%, the mass fraction of the lubricant is 0.5-2%, and the rest is a type-one resin, wherein the type-one resin is PBAT resin, and the type-two resin is a non-crystalline resin compatible with the PBAT resin.

[0005] In a preferred embodiment of the present invention, the second type of resin is a combination of one or more of PETG, PCTG, and PC.

[0006] In a preferred embodiment of the present invention, the Vicat softening temperature of the material after crystallization is greater than 75°C.

[0007] In a preferred embodiment of the present invention, the foaming agent is a microsphere foaming agent or a carbonate foaming agent, or a combination of both.

[0008] In a preferred embodiment of the present invention, the lubricant is one or more of E wax, fatty acid or fatty acid ester.

[0009] In order to solve the above technical problems, a technical solution adopted by the present invention is: to provide a method for preparing a high-toughness and high-temperature-resistant foam material for FDM technology, the method for preparing a high-toughness and high-temperature-resistant foam material for FDM technology comprises the following steps:

[0010] Step 1. The first type of resin and the second type of resin are uniformly mixed in a mixer to obtain material A, and then material A and part of the flow modifier are simultaneously added into a twin-screw extruder for blending, melt extrusion, stranding and cooling and pelletizing to obtain masterbatch B;

[0011] Step 2. After the masterbatch B, the foaming agent and the remaining flow modifier are mixed, they are melt-extruded through a single-screw extruder under the processing condition of a processing temperature of ≤200°C, and then drawn into a wire, cooled and shaped to obtain a finished wire.

[0012] In a preferred embodiment of the present invention, the finished wire is a round wire, and the density of the finished wire is ≥1.1g / cm 3 .

[0013] In a preferred embodiment of the present invention, the amount of lubricant used in step 1 is not less than 3 / 4 of the total amount of lubricant used.

[0014] The beneficial effects of the present invention are as follows: the high-toughness, high-temperature-resistant foam material based on PBAT resin in the present invention not only has good processing characteristics, remains stable and will not be excited during the processing, but also can automatically adjust the foaming ratio of the material as the parameters of 3D printing change during the printing process, thereby meeting the requirements for different densities of the product. At the same time, the material has good thermal insulation, cushioning, and high temperature resistance. In addition, the foam material of the present application can be transformed between soft foam material and hard foam material in terms of mechanical properties by adjusting the formula, replacing the use of PLA-based materials in some fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is the DSC scanning result of Comparative Example 2 in the present invention. DETAILED DESCRIPTION

[0016] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0017] The embodiments of the present invention are as follows:

[0018] Example 1

[0019] This embodiment provides a high-toughness, high-temperature resistant foam material. The high-toughness, high-temperature resistant foam material comprises the following components by mass fraction:

[0020]

[0021] The preparation method of the high-toughness high-temperature resistant foam material of the above components is as follows:

[0022] Step 1. Place PBAT and PC plastic particles in a dryer at 100°C for 4 hours for drying. After drying, put PBAT and PC into a mixer in proportion and stir to obtain material A. Put the mixed material A into the main feeding barrel of a twin-screw extruder, and put pentaerythritol stearate into the side feeding barrel of the twin-screw extruder. After melt extrusion by the twin-screw extruder, draw the strips, cool and pelletize to obtain modified particles B. In this process, the feed ratio of material A: pentaerythritol stearate is 94:1.5 and mixed evenly.

[0023] Step 2. First, place the modified particle B in a dryer at 80°C, 4 for drying. After drying, put the particle B, pentaerythritol stearate, and microsphere foaming agent powder into a mixer at a mass ratio of 95.5:0.5:4 and mix them evenly. During the mixing process, particle B has just been dried at high temperature, and the surface temperature is relatively high, close to 80°C. Pentaerythritol stearate will melt after heating, and after stirring, it will adhere to the surface of particle B. At the same time, the molten pentaerythritol stearate can bond the microsphere foaming agent powder to the surface of particle B, achieving uniform mixing of particles and powder. Finally, the mixed material is put into a single-screw extruder, and is formed into a wire after melt extrusion, wire drawing, and cooling and shaping. The processing temperature of the single-screw extruder during extrusion is ≤180°C Example 2

[0024] This embodiment provides a high-toughness, high-temperature resistant foam material. The high-toughness, high-temperature resistant foam material comprises the following components by mass fraction:

[0025] PBAT 84%,

[0026] PC 15%,

[0027] Microsphere foaming agent 4%,

[0028] Pentaerythrityl stearate 2%

[0029] The preparation method of the high-toughness high-temperature resistant foam material of the above components is as follows:

[0030] step1. Place PBAT and PC plastic particles in a dryer at 100°C for 4 hours for drying. After drying, put PBAT and PC into a mixer in proportion and stir to obtain material A. Put the mixed material A into the main feeding barrel of a twin-screw extruder, and put pentaerythritol stearate into the side feeding barrel of the twin-screw extruder. After melt extrusion by the twin-screw extruder, draw the strips, cool and pelletize to obtain modified particles B. In this process, the feed ratio of material A: pentaerythritol stearate is 94:1.5.

[0031] Step 2. First, place the modified particle B in a dryer at 80°C, 4 for drying. After drying, put the particle B, pentaerythritol stearate, and microsphere foaming agent powder into a mixer at a mass ratio of 95.5:0.5:4 and mix them evenly. During the mixing process, since the particle B has just been dried at high temperature, the surface temperature is relatively high and close to 80°C. The pentaerythritol stearate will melt after being heated, and after stirring, it will adhere to the surface of the particle B. At the same time, the molten pentaerythritol stearate can bond the microsphere foaming agent powder to the surface of the particle B, so as to achieve uniform mixing of the particles and the powder. Finally, the mixed material is put into a single-screw extruder, and is formed into a wire after melt extrusion, wire drawing, and cooling and shaping. The processing temperature of the single-screw extruder during extrusion is ≤180°C Example 3

[0032] This embodiment provides a high-toughness, high-temperature resistant foam material. The high-toughness, high-temperature resistant foam material comprises the following components by mass fraction:

[0033] PBAT 61%,

[0034] PC 33%,

[0035] Carbonate foaming agent 4%,

[0036] Pentaerythrityl stearate 2%

[0037] The preparation method of the high-toughness high-temperature resistant foam material of the above components is as follows:

[0038] step1. Place PBAT and PC plastic particles in a dryer at 100°C for 4 hours for drying. After drying, put PBAT and PC into a mixer in proportion and stir to obtain material A. Put the mixed material A into the main feeding barrel of a twin-screw extruder, and put pentaerythritol stearate into the side feeding barrel of the twin-screw extruder. After melt extrusion by the twin-screw extruder, draw the strips, cool and pelletize to obtain modified particles B. In this process, the feed ratio of material A: pentaerythritol stearate is 94:1.5.

[0039] Step 2. First, place the modified particle B in a dryer at 80℃, 4 for drying. After drying, put the particle B, pentaerythritol stearate, and microsphere foaming agent powder into a mixer at a mass ratio of 95.5:0.5:4 and mix them evenly. During the mixing process, since the particle B has just been dried at high temperature, the surface temperature is high and close to 80℃. The pentaerythritol stearate will melt after heating. After stirring, it will adhere to the surface of the particle B. At the same time, the molten pentaerythritol stearate can bond the microsphere foaming agent powder to the surface of the particle B, so as to achieve uniform mixing of the particles and powder. Finally, the mixed materials are put into a single screw extruder, and the wire is formed after melt extrusion, wire drawing, cooling and shaping. The processing temperature of the single screw extruder during the extrusion process is ≤180℃.

[0040] According to the above steps, a comparative example is prepared as follows:

[0041] Comparative Example 1

[0042] The mass fractions of each component are as follows:

[0043] PBAT 84%,

[0044] PC 6%,

[0045] Microsphere foaming agent 4%,

[0046] The above components are prepared into printing wire according to the following method:

[0047] Step 1. Place PBAT and PC plastic particles in a dryer at 100°C for 4 hours for drying. After drying, put PBAT and PC into a mixer according to the proportion and stir to obtain material A. Put the mixed material A into a twin-screw extruder, melt-extrude it through the twin-screw extruder, draw it into strips, cool it, and cut it into pellets to obtain modified particles B.

[0048] Step 2. First, place the modified particles B in a dryer at 80°C, 4 for drying. After drying, put the particles B, pentaerythritol stearate and microsphere foaming agent powder into a mixer at a mass ratio of 94:4 and mix them evenly. Finally, put the mixed materials into a single screw extruder, and form wires after melt extrusion, wire drawing, cooling and shaping. Since no lubricant is added to the components of this embodiment, during the processing of the single screw extruder, the processing temperature is ≥220°C, and the plastic particles and the foaming agent powder are mixed unevenly, so that the foaming agent in the wire begins to foam to form bubbles, and the wire diameter is uneven.

[0049] Comparative Example 2

[0050] The mass fractions of each component in the embodiment are as follows:

[0051]

[0052]

[0053] The difference between this comparative example and the embodiment is that the formula ratio is changed, and the addition amount of the second type of resin exceeds the preferred range. The processing method is as follows:

[0054] step1. Place PBAT and PC plastic particles in a dryer at 100°C for 4 hours for drying. After drying, put PBAT and PC into a mixer in proportion and stir to obtain material A. Put the mixed material A into the main feeding barrel of a twin-screw extruder, and put pentaerythritol stearate into the side feeding barrel of the twin-screw extruder. After melt extrusion by the twin-screw extruder, draw the strips, cool and pelletize to obtain modified particles B. In this process, the feed ratio of material A: pentaerythritol stearate is 94:1.5.

[0055] Step 2. First, place the modified particle B in a dryer at 80℃, 4 for drying. After drying, put the particle B, pentaerythritol stearate, and microsphere foaming agent powder into a mixer at a mass ratio of 95.5:0.5:4 and mix them evenly. During the mixing process, since the particle B has just been dried at high temperature, the surface temperature is high and close to 80℃. The pentaerythritol stearate will melt after heating. After stirring, it will adhere to the surface of the particle B. At the same time, the molten pentaerythritol stearate can bond the microsphere foaming agent powder to the surface of the particle B, so as to achieve uniform mixing of the particles and powder. Finally, the mixed materials are put into a single screw extruder, and the wire is formed after melt extrusion, wire drawing, cooling and shaping. The processing temperature of the single screw extruder during the extrusion process is ≤180℃.

[0056] The wires obtained in Examples 1, 2, 3 and Comparative Examples 1 and 2 were used to print standard samples using a BamBu brand X1C printer.

[0057] 1) Test the Vicat softening temperature of the sample according to the test standard GB / T 1633 "Determination of Vicat softening temperature (VST) of thermoplastics". The printing temperature is 190℃, the printing speed is 60mm / s, and the material does not foam during the printing process.

[0058] 2) Test the hardness of the printed sample according to GB / T 531 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber". The printing temperature is 190℃, the printing speed is 60mm / s, and the material does not foam during the printing process.

[0059] 3) The unnotched impact strength of the printed sample was tested according to the standard GB / T 1043 "Hard Plastic Simple Supported Beam Impact Test Method", using sample type 1. The printing temperature was 190°C, the printing speed was 60mm / s, and the material did not foam during the printing process.

[0060] 4) Density test method: Print a 40mm*40mm*40m cube with a filling rate of 100%, a printing speed of 60mm / s, a printing temperature of 190-270℃, and a temperature gradient of 10℃. At each temperature, adjust the printing flow setting to ensure that the printed surface of each layer of the model remains flat, without gaps or protrusions. It appears as a solid cube on a macro scale. The density of the cube is calculated by the mass volume method, which is the density of the filament after printing and foaming. See the table below for details:

[0061] Table 1 Summary of test results:

[0062]

[0063] From the comparison of Example 1 with Example 2 and Example 3 in the above test results, it can be seen that the increase in the PC content of the second type of resin can gradually increase the hardness of the material, and at the same time the temperature resistance of the material will be reduced to a certain extent. From Comparative Example 1, it can be seen that due to the lack of lubricant, the viscosity of the material is relatively high. Although it can be melt-extruded into wire by increasing the processing temperature, the foaming agent will foam prematurely, which will ultimately affect the quality of the wire. From the comparison of Examples 1, 2, 3 and Comparative Example 2, it can be seen that when the PC content is high (>35%), the temperature resistance of the material will be greatly reduced. Through literature analysis, PC and PBAT are prone to ester exchange reactions during the melt blending process, thereby reducing various aspects of performance. The material was subjected to DSC scanning analysis (see Figure 1 ) shows that the cooling crystallization peak of the material is weak, indicating that the addition of a large amount of PC reduces the cooling crystallization ability of PBAT; at the same time, the good compatibility of PBAT and PC causes the glass transition temperature of PC to shift to low temperature, and the original glass transition temperature of PC should be around 140°C. The combined effect of poor crystallization ability and low glass transition temperature ultimately leads to a significant reduction in the heat resistance of the material.

[0064] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A high-toughness, heat-resistant foam material for FDM printing, characterized in that: The components of the high-toughness, temperature-resistant foaming material include: a type-one resin, a type-two resin, a foaming agent and a lubricant, wherein the mass fraction of the type-two resin is 5-35%, the mass fraction of the foaming agent is 3-10%, the mass fraction of the lubricant is 0.5-2%, and the rest is the type-one resin, the type-one resin is PBAT resin, and the type-two resin is a non-crystalline resin compatible with the PBAT resin.

2. The high-toughness, heat-resistant foam material for FDM printing according to claim 1, characterized in that: The second type of resin is a combination of one or more of PETG, PCTG and PC.

3. The high-toughness, temperature-resistant foam material for FDM printing according to claim 1, characterized in that: The Vicat softening temperature of the material after crystallization is greater than 75°C.

4. The high-toughness, heat-resistant foam material for FDM printing according to claim 1, characterized in that: The foaming agent is a microsphere foaming agent or a carbonate foaming agent, or a combination of the two.

5. The high-toughness, heat-resistant foam material for FDM printing according to claim 1, characterized in that: The lubricant is one or more of E wax, fatty acid or fatty acid ester.

6. A method for preparing a high-toughness and high-temperature-resistant foam material for FDM technology according to any one of claims 1 to 5, characterized in that: The method for preparing the high-toughness and high-temperature-resistant foaming material for FDM technology comprises the following steps: Step 1. The first type of resin and the second type of resin are uniformly mixed in a mixer to obtain material A, and then material A and part of the flow modifier are simultaneously added into a twin-screw extruder for blending, melt extrusion, stranding and cooling and pelletizing to obtain masterbatch B; Step 2. After the masterbatch B, the foaming agent and the remaining flow modifier are mixed, they are melt-extruded through a single-screw extruder under the processing condition of a processing temperature of ≤200°C, and then drawn into a wire, cooled and shaped to obtain a finished wire.

7. The high-toughness, heat-resistant foam material for FDM printing according to claim 6, characterized in that: The finished wire is a round wire, and the density of the finished wire is ≥1.1g / cm 3 .

8. The high-toughness, heat-resistant foam material for FDM printing according to claim 6, characterized in that: The amount of lubricant used in step 1 is not less than 3 / 4 of the total amount of lubricant used.

Citation Information

Patent Citations

  • Microporous foam 3D (three-dimensional) printing polymer consumable and method and production device for preparing microporous foam 3D printing polymer consumable

    CN107254151A

  • Intelligent high polymer material as well as preparation method and utilization method thereof

    CN109456565A